2016
DOI: 10.4103/1119-3077.173714
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function tests in patients with Parkinson's disease: A case-control study

Abstract: In this study, the values of the evaluated PFTs (VC, FEV1, FEV1/VC, and PEFR) parameters were significantly lower in PD compared with age- and sex-matched control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 0 publications
1
23
0
5
Order By: Relevance
“…Parkinson's disease patients can experience an impairment in the tone, contractility and coordination of the thoracic musculature, affecting both respiratory mechanics and pulmonary functions (Baille et al., ; Owolabi et al., ; Reyes, Ziman, & Nosaka, ). Therefore, studies that evaluate the respiratory mechanics in a model of PD might lead to greater understanding of the effects of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Parkinson's disease patients can experience an impairment in the tone, contractility and coordination of the thoracic musculature, affecting both respiratory mechanics and pulmonary functions (Baille et al., ; Owolabi et al., ; Reyes, Ziman, & Nosaka, ). Therefore, studies that evaluate the respiratory mechanics in a model of PD might lead to greater understanding of the effects of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also found that PD patients showed a reduction of pulmonary volumes and stiffening of respiratory muscles, indicating an impairment directly in the lung, ribcage and/or the muscles responsible for breathing (Baille et al., ; LeWitt et al., ; Owolabi et al., ; Seccombe et al., ). Additionally, clinical reports describe a predisposition to development of lung infections by PD patients, and to embolism and allergic reactions, compared with the general population (Hampson, Kieburtz, LeWitt, Leinonen, & Freed, ; Letsiou et al., ; Owolabi et al., ). Furthermore, areas in the brain responsible for the operation of swallowing and coughing movements can be downregulated in PD; therefore, lung infections in those patients could be associated with dysphagia (Hinkel et al., ; Schiffer & Kendall, ; van Hooren et al., ).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although there have been numerous studies of pulmonary function in PD, few have investigated the contributions of central and peripheral respiratory mechanisms using functional respiratory testing in patients with dyspnea. Table summarizes the key studies addressing pulmonary dysfunction in PD and shows the frequency of restrictive and obstructive patterns . Review of these studies shows a lack of consistent findings, which is likely due to the fact that they included diverse cohorts of patients at different stages of disease and used variable outcome measures.…”
Section: Studies Of Pulmonary Function In Pdmentioning
confidence: 99%